고령의 비소세포폐암(Non-small cell lung cancer) 환자를 대상으로 한 한양방 복합 치험 2례 - 진수현; 진하윤; 이민준; 최대준; 이범준; 정희재; 김관일; Su-hyun Chin; Hayun Jin; Min-jun Lee; Dae-jun Choi; Beom-joon Lee; et al. (대한한방내과학회지, 2025)
Background: Non-small-cell lung cancer (NSCLC) accounts for 84% of all lung cancers, and advancements in treatment methods have significantly improved the survival rate of NSCLC patients. However, up to 60% of NSCLC patients experience debilitating symptoms, such as fatigue, pain, and psychological distress, particularly in elderly populations. Palliative care, including complementary approaches such as traditional Korean medicine, has gained attention for alleviating treatment-related complications and improving quality of life. Case Presentation: Two elderly NSCLC patients who had undergone surgery with or without chemotherapy and radiotherapy were treated with traditional Korean medicine. The first case involved a 78-year-old female who presented with a loss of appetite, cough, and dizziness following surgery. Her treatment included Yikgeebohyul-tang, acupuncture, Chuna therapy, cupping, and herbal steam therapy. Post-treatment, improvements were observed in her appetite, quality of life, and fatigue levels. The second case involved a 79-year-old male patient who presented with decreased energy, upper limb weakness with pain, and constipation while undergoing chemotherapy and radiotherapy. He was treated with various herbal formulas (Hyungbangjihwang-tang, Saengsukjihwang-tang, Yanggyeoksanhwa-tang, Jihwangbaekho-tang, and Chungpaesagan-tang), acupuncture, and electroacupuncture. Post-treatment, improvements were observed in his energy levels, upper limb pain, and constipation. Conclusion: These cases suggest that integrating TKM with conventional therapies may reduce treatment-related complications, improve symptom management, and enhance adherence to chemotherapy/radiotherapy through complementary effects in elderly patients. Further studies are warranted to validate these observations in broader populations.